An analysis of institutional structures, organisational culture and decision-making processes that affect the sustainability of buildings at the University of Cape Town - Mandalia, Jigisha (Energy Research Centre, 2018)
Universities globally are realising the potential they have in shaping the future workforce to deal with a variety of environmental issues, such as efficient resource use and sustainable development. The University of Cape Town (UCT) has committed to a number of environmental sustainability goals and is a signatory to international sustainable campus charters. This dissertation analyses the progress of sustainability levels of buildings on campus. A case study of three recently built buildings was undertaken, the last of which attained a 4-star green rating by the Green Building Council of South Africa. A detailed analysis was conducted through semi-structured interviews with key stakeholders at the university and others, including architects and sustainability experts. This study specifically evaluates the institutional structures, organisational culture and decision-making processes that have enabled, promoted or hindered sustainable buildings at UCT. One key policy was established in 2012, which stated that all new buildings at UCT will be constructed to be 4-star rated at a minimum. The decisions leading up to this policy were analysed and they highlight the enabling mechanisms within the university. However, a number of barriers and challenges were found that hindered progress. Many challenges are not unique given the similarity of university structures and governance globally, such as lack of: resources, awareness, motivation and coordination. However, there are local and contextual challenges, especially lack of funding and competing priorities, that need to be addressed before sustainability is fully integrated into UCT. Moreover, inertia of large institutions, difficulty in shifting organisational culture, and complex and lengthy decision-making processes make change difficult at a university. Nevertheless, some strategies are explored that are likely to be effective in promoting increased sustainability levels, especially of buildings on campus.